An Ocean Declaration for equitable governance to guide observation - Yoshitaka Ota; Gerald G. Singh; Andrés M. Cisneros-Montemayor; Eliana Ritts; Matthew J. Schneider; Ana Spalding; Mia Strand; Wilf Swartz; Alexis Valauri-Orton (npj Ocean Sustainability)
The Dubai Ocean Declaration is the latest international call to expand ocean observation worldwide. We argue that there needs to be a committed effort to establish governance systems to guide data collection designed around equity, to ensure ocean data collection contributes to sustainable development. Ocean science has historically been led by the Global North, neglecting the priorities and leadership of the Global South, and limiting the relevance of ocean science for global sustainability.